Dynamic Dependence Structure between Chinese Stock Market Returns and RMB Exchange Rates. Issue 15 (8th December 2019) - Li, Rong; Hu, Zongyi; Li, Sufang; Yu, Keming
ABSTRACT: This paper investigates the dynamic dependence structure between the Chinese stock market and the real exchange rate of the Chinese renminbi (RMB) with unconditional and conditional copula models for the period July 22, 2005, to December 31, 2017. The results show that the crisis induced significant structural breaks, and the relationship is weak before the global financial crisis but substantially stronger after the financial crisis, regardless of whether the correlation is positive or negative. Our findings have important implications for global portfolio diversification, risk management, and China's exchange rate policy.